PENGARUH BEBAN KERJA TERHADAP KINERJA TIM LAPANGAN DI PHENOM EVENT INDONESIA - Kadek Doni Dwiartha Putra; Ratri Paramita; Ketut Arjaya (Journal of Event and Convention Management, 2023)
The high workload faced by event organizers, especially field teams, can affect the performance of field teams. This study aims to determine the effect of the workload faced by the Phenom Event Indonesia field team. The research uses workload theory according to Achyana (2016) which includes working conditions, use of working time, and targets to be achieved. This study also uses the theory of employee performance according to Robbins (2006) covering quality, quantity, timeliness, effectiveness, independence and work commitment. The method used in this research is quantitative descriptive analysis. The total population in this study is 9 people using a saturated sample. Data were collected using questionnaires and interviews. The results of this research indicate that the workload variable gets an average value of 2,555 (light workload). On the performance variable the field team got an average value of 1,777 (very good performance). The average value of the two variables shows that light workload causing the field team’s performance to be very good.